Optimization Design of the High-speed Gear Web Structure of Electric Vehicles Based on Numerical Simulation - Wang Peng; Yu Lei; Huang Chao (Jixie chuandong)
With the increasing demand of noise-vibration-harshness(NVH) performance of the electric vehicle drive system, higher requirements are put forward for gear design in the electric drive system. Based on numerical simulation, in this study, the gear web design of the wheel of an offset gearbox for the electric drive system is optimized. From mode of vibration, tooth root stress, transmission error to manufacturing error sensitivity, five kinds of gear web designs are analyzed, including simple plate, simple plate with weight reduction bore, simple plate with curved oval bore, simple plate with ribs and complex plate. The results show that with the complex plate design, the mode of vibration, tooth root stress, transmission error and manufacturing error sensitivity of the wheel can all be improved, especially for the natural frequency, which is significantly improved compared with the other four designs. The staggered plate spoke structure optimized using the method described in this study, under the same quality conditions, compared to the common circular weight reduction hole plate structure, increases the first modal frequency of the gear by 72% and reduces the transmission error by 18%. This can effectively avoid the high-speed gear whistling problem caused by large gear resonance.